Construction of complex Co3O4@Co3V2O8 hollow structures from metal-organic frameworks with enhanced lithium storage properties - Lu, Yan (2020)
A novel metal-organic-framework-engaged strategy is demonstrated for the preparation of multishelled Co3 O4 @Co3 V2 O8 hybrid nanoboxes. This strategy relies on the unique reaction of zeolitic imidazolate framework-67 with the vanadium source of vanadium oxytriisopropoxide. Benefitting from the synthetic versatility, a series of nanostructures can be realized including triple-shelled and double-shelled Co3 O4 @Co3 V2 O8 nanoboxes and single-shelled Co3 V2 O8 nanoboxes. When evaluated as electrode materials for lithium-ion batteries, these unique hollow structures demonstrate remarkable lithium storage properties. For example, the triple-shelled Co3 O4 @Co3 V2 O8 nanoboxes retain a high capacity of 948 mAh g-1 after 100 cycles at 100 mA g-1.